Online charging for services in communication network based on user-related context : : doctoral thesis - Grgić, Tomislav (T. Grgić ; Fakultet elektrotehnike i računarstva, 2013)
ABSTRACT: The state-of-the-art charging systems utilize only a limited subset of the overall user information available in a mobile network. This thesis aims to fill this gap by addressing the problem of how to include a broader contextual information regarding users in the process of online charging. The goal of the research is to utilize the notion of recognizing certain charging events (e.g., credit depletion during an upcoming time interval) for the purpose of making timely service adaptation decisions. The motivation is to provide an ability to prevent premature service termination, ultimately increasing user experience and overall satisfaction. In order to achieve this goal, the thesis proposes extensions to the online charging functionality. The new functionality monitors the user context (e.g., active services or credit depletion rate during the given time interval), and notifies the related network function of the incoming event(s). The User-related Charging Context is introduced in the mobile network, which specifies the relevant user information, proposes how it is managed, considers data privacy limitations, and determines the sources of information considering the current 3GPP network specifications. Next, the thesis introduces the Context monitoring process that takes place during the online charging process and interacts with it. The context monitoring process monitors the relevant context, and undertakes actions in response to the detected events. Necessary extensions to relevant network functions and to the Diameter-based reference points are also proposed, particularly the extensions to the charging system. The model is mapped to the 3GPP network architecture. The use case illustrates the feasibility of the proposed approach and validates it, regarding the reduced number of premature service terminations. Finally, the results achieved by using the extended charging functionality are compared with the results achieved by using the standard charging functionality (as defined by 3GPP). It has been demonstrated that the likelihood of the premature service termination is reduced when the extended functionality is used. -